Persepsi Pengguna Sepeda terhadap Penerapan Jalur Sepeda di Kota Jambi - Dyah Kumalasari; Ade Nurdin; Titania Oktaviani (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
The more bike users in Indonesia, so the government issued a rule of no government. 59 years 2020 about the cycle-line criteria and the safety of bicycle patterns, published with the intent to create traffic orderly and maintain the safety of a bicycle vehicle. One of the bike paths in Jambi City is the bike path of Soemantri Bojonegoro which was officially officially on December 20 by Mayor Jambi. This research aims to know the perception of bicycle users to apply to the application of the Jambi City. The data collection technique used is a survey method by using direct quisitioners and measured with Likert Scale with Microsoft Excel. TCR criteria or bicycle access levels for each bicycle experience are good enough, bicycle security is good enough, bicycle signature and good parking is good enough. With this to see the whole value or criteria of the levels of cycle use in Jambi City is quite adequate and worthy to use the bicycle paths in the path of 69.66% of the average of the TCR. is quite well that the perception of the bicycle users are well enough to use the bicycle paths in the path of the Jambi City are well enough to use the bicycle users in the path of the up.